Balancing Competing Logics in For-Profit Social Enterprises: A Need for Hybrid Governance. Issue 3 (1st September 2016) - Bruneel, Johan; Moray, Nathalie; Stevens, Robin; Fassin, Yves
Abstract: This paper reports a case study of a for-profit award-winning social enterprise that faced bankruptcy two years after founding. The findings show that the firm's overemphasis on the social employment logic and the increasing disregard of the commercial market logic led to the failure. This imbalance in response to the two competing logics was fuelled by the entrepreneurs' strong social values, stakeholder reinforcement, and lack of appropriate governance. This study shows that hybrid organizations need to pay attention to the governance of the tension between competing demands inside as well as outside the organization. Hybrid organizations therefore require a hybrid governance model. By presenting a case of failure of a social enterprise, the paper counterbalances the dominance of optimistic idealism in social entrepreneurship literature.